2011
DOI: 10.1002/jobm.201000517
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a protease produced by Bacillus megaterium RRM2: application in detergent and dehairing industries

Abstract: An alkaline serine protease produced by Bacillus megaterium RRM2 isolated from the red alga, Kappaphycus alvarezii (Doty) Doty ex Silva was studied for the first time and the same analyzed for the production of protease in the present study. Identification of the bacterium was done on the basis of both biochemical analysis and by 16S rDNA sequence analysis. The extracellular protease obtained from B. megaterium RRM2 was purified by a three-step process involving ammonium sulphate precipitation, gel filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 34 publications
3
16
1
1
Order By: Relevance
“…The enzyme was found to be stable upto pH 9 for 1 h. Results of similar trend were observed by other researchers when characterizing Bacillus sp. producing proteolytic and keratinolytic enzymes (Rajkumar et al, 2011;El-Hadj-Ali et al, 2007;Haile and Gessesse, 2012). Rao et al (1998) have reported that the commercial bacterial keratinolytic enzymes have pH optima in the range from 8 to 12 and the results of the present study also found in line with his findings.…”
Section: Resultssupporting
confidence: 91%
“…The enzyme was found to be stable upto pH 9 for 1 h. Results of similar trend were observed by other researchers when characterizing Bacillus sp. producing proteolytic and keratinolytic enzymes (Rajkumar et al, 2011;El-Hadj-Ali et al, 2007;Haile and Gessesse, 2012). Rao et al (1998) have reported that the commercial bacterial keratinolytic enzymes have pH optima in the range from 8 to 12 and the results of the present study also found in line with his findings.…”
Section: Resultssupporting
confidence: 91%
“…Also it was compatible with all surfactants found in commercial detergent (Ariel), which indicates its potential candidate in detergent formulation. This result is well established by many authors [25,28,30]. Such practice may find application in removing blood stains from materials of medical importance.…”
Section: Discussionsupporting
confidence: 69%
“…Maximum loss of enzymatic activity was observed in Fe +2 . The presence of Ca 2+ did not affect the enzyme activity [28]. However, in another report, metal ions like Mn 2+ and Ca 2+ were found to be potent enhancers [29].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In other bacterial strains also found on Sargassum sp., amylase, carboxymethylcellulase, and protease activities were found (Mohapatra et al 2003). An alkaline serine protease with potential use in the laundry industry was found in Bacillus megaterium RRM2, isolated from a red alga species (Rajkumar et al 2011). Furthermore, bacterial enzymes such as lipases and esterases (Rajkumar et al 2011), cellulases (Dong et al 2010;Fu et al 2010;Gibbs et al 1992), proteases (Cristóbal et al 2011;Yang et al 2013), amylases (Both et al 1993;Liu et al 2012), laccases (Fang et al 2012;Ge et al 2011), and beta-glucosidases (Cristóbal et al 2009;Mai et al 2013), distantly related to terrestrial ones and displaying original biochemistry, are increasingly being isolated from the marine environment.…”
Section: Microorganisms Enhance Algal Defense Growth and Nutrient Umentioning
confidence: 99%